The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1128/aac.00850-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibiotic Synergy in Extensively Drug-Resistant Acinetobacter baumannii : the Effect of Testing by Time-Kill, Checkerboard, and Etest Methods

Abstract: Treatment of extensively drug-resistant (XDR) Acinetobacter baumannii infections is challenging because of both the limited choice of antibiotic and the tendency of such infections to occur in critically ill hosts with limited physiologic reserves (17). Polymyxins demonstrate in vitro activity against A. baumannii, but resistance is also reported (8,17). In the absence of feasible alternatives, unconventional antibiotics, such as minocycline, rifampin, and tigecycline, have been used, both singly and in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 16 publications
1
24
0
4
Order By: Relevance
“…Time-kill assay is very laborious if a high number of combinations are required, and the results are greatly influenced by differences on the inoculum size and on the interpretation of the results (because relatively few antibiotic concentrations are examined) (White et al, 1996). Also, methods for the interpretation of kill-kinetic studies vary, and synergy has been defined by some authors as at least a 100-fold increase in killing at 24 h (Bonapace et al, 2000;Jung et al, 2004;Kiraz et al, 2009;Mayer and Nagy, 1999), while other authors consider a 200-fold increase (Guo et al, 2008;Leonard, 2012;Tan et al, 2011). Relatively to checkerboard, the endpoint (i.e., the complete inhibition of growth) is a qualitative measure (Tariq et al, 1995), and the occurrence of synergy appears to be highly dependent on the method of interpretation (Bonapace et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Time-kill assay is very laborious if a high number of combinations are required, and the results are greatly influenced by differences on the inoculum size and on the interpretation of the results (because relatively few antibiotic concentrations are examined) (White et al, 1996). Also, methods for the interpretation of kill-kinetic studies vary, and synergy has been defined by some authors as at least a 100-fold increase in killing at 24 h (Bonapace et al, 2000;Jung et al, 2004;Kiraz et al, 2009;Mayer and Nagy, 1999), while other authors consider a 200-fold increase (Guo et al, 2008;Leonard, 2012;Tan et al, 2011). Relatively to checkerboard, the endpoint (i.e., the complete inhibition of growth) is a qualitative measure (Tariq et al, 1995), and the occurrence of synergy appears to be highly dependent on the method of interpretation (Bonapace et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Most synergy studies against A. baumannii, however, are conducted in vitro by applying time-kill or checkerboard methodology, where only specific fixed concentrations of antibiotics are studied. Using this methodology, numerous studies have observed synergistic interactions between polymyxins and various other antibiotic classes, including carbapenems, tigecycline, rifampin, and most recently, vancomycin (15)(16)(17)(18)(19)(20)(21)(22). These time-kill and checkerboard experiments, however, ignore the contribution of human pharmacokinetics and the dynamic effects of varied drug concentrations over the duration of the experiment.…”
mentioning
confidence: 99%
“…The highest synergy was seen in beta-lactam-fluoroquinolone and fluoroquinolone-AK combinations. 24 While in a study conducted in 2011, Tan et al 8 detected rate of synergy by CB method between polymyxin B-RF and TGC-RF as 19%, those between polymyxin B-TGC was 12%. The same rates obtained by TK methods were 56%, 19% and 44% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1 Of these alternative classes, polymyxin and tigecycline (TGC) remain the most active treatments in vitro against MDR A. baumannii but resistance against these antibiotics is also reported. 4,6,7,8 Combination therapy is often used in the treatment of MDR A. baumannii infections to prevent the emergence of resistance and obtain a synergistic effect. 1,3,8 The aim of this study was to determine the antimicrobial resistance profile, clonal relation and efficacy of antimicrobial combinations on nosocomial MDR A. baumannii.…”
Section: Introductionmentioning
confidence: 99%